Computational screening for novel α-glucosidase inhibitory peptides from Chlamys nobilis adductor muscle as a potential antidiabetic agent - Lin, Haisheng; Wang, Wen; Du, Lei; Gao, Jialong; Cao, Wenhong; Zheng, Huina; Chen, Zhongqin; Qin, Xiaoming; Liang, Yuanwei (Frontiers in Nutrition, 2025)
IntroductionThis study aimed to evaluate the adjuvant hypoglycemic function of enzyme hydrolyzate (EHCA) from Chlamys nobilis in mice and to identify α-glucosidase inhibitory peptides.MethodsThe α-glucosidase inhibitory and radical scavenging ability of EHCA were determined in vitro, and the effects on blood glucose regulation and the antioxidant activity were evaluated in vivo using a mouse model. Peptides with potential α-glucosidase inhibitory activity were identified by LC-MS/MS and confirmed in silico.Results and DiscussionEHCA exhibited significant α-glucosidase inhibitory activity and radical scavenging activity against 2,2-diphenyl-1-picrylhydrazyl (DPPH). in vivo, EHCA significantly improved the glucose tolerance of mice, reduced malondialdehyde and increased the superoxide dismutase activity in liver. Five novel peptides were identified, with Lys-Leu-Asn-Ser-Thr-Thr-Glu-Lys-Leu-Glu-Glu and Thr-Asp-Ala-Asp-His-Lys-Phe showing strong inhibitory effects on α-glucosidase (IC50 value of 144.89 μM and 136.96 μM, respectively). The interactions between peptides and α-glucosidase were driven by hydrogen bonds, van der Waals forces, and hydrophobic interactions. These findings suggest that EHCA and its derived peptides could serve as potential adjuvant agents for blood glucose regulation and antioxidant activity. The identified peptides may pave the way for the development of alternative α-glucosidase inhibitors.